1974
DOI: 10.2337/diab.23.8.708
|View full text |Cite
|
Sign up to set email alerts
|

Phytohemagglutinin Transformation and Circulating Lymphocyte Subpopulations in Insulin-dependent Diabetic Patients

Abstract: The lymphocyte transformation response to the mitogen phytohemagglutinin (PHA) was determined in forty well controlled insulin-dependent diabetics, forty matched normal subjects and fourteen poorly controlled insulin-dependent diabetics. There was no significant difference in the PHA responses of normal subjects and well controlled diabetics, but poorly controlled diabetics showed a marked depression of lymphocyte transformation.Peripheral blood T and B lymphocyte subpopulations were also measured in fifteen n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
2
4

Year Published

1978
1978
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(78 citation statements)
references
References 6 publications
4
68
2
4
Order By: Relevance
“…Detailed study of cell-mediated immunity (CMI), predominately T-lymphocyte function, has identified specific defects in poorly controlled type 1 patients [29,30]. However, in a recent in vitro study involving type 1 patients, all with a HbA 1c <8.0% [31], there were impaired proliferative CD4+ cell responses to primary protein antigens, perhaps due to altered expression of cellular adhesion molecules and/or reduced cytokine release independent of glycaemia [32].…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…Detailed study of cell-mediated immunity (CMI), predominately T-lymphocyte function, has identified specific defects in poorly controlled type 1 patients [29,30]. However, in a recent in vitro study involving type 1 patients, all with a HbA 1c <8.0% [31], there were impaired proliferative CD4+ cell responses to primary protein antigens, perhaps due to altered expression of cellular adhesion molecules and/or reduced cytokine release independent of glycaemia [32].…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…However, there are some data to suggest that it could, in part, relate to a compromised immune system. Short-and long-term hyperglycemia may disturb immune functions such as neutrophil bactericidal function (13), cellular immunity (14), and complement activation (15). These defects in the immune system, along with vascular insufficiency, render patients with diabetes at higher risk for a variety of severe or invasive infections compared with those without diabetes (16).…”
mentioning
confidence: 99%
“…The number of circulating helper (CD4) cells is reduced [2], the helper/suppressor (CD4/CD8) lymphocyte ratio is decreased [3,4], phagocytic activity is impaired [5] and lymphocyte blastogenesis is reduced [6]. These are amongst the most consistent alterations reported in vitro and may well account for the greater susceptibility to infection in patients with poor metabolic control [7].…”
mentioning
confidence: 99%